Volume changes in the contralateral submandibular gland following unilateral gland excision in oral cancer patients - Yei-Jin Kang; Young-Wook Park; Hang-Moon Choi; Seong-Gon Kim (Maxillofacial Plastic and Reconstructive Surgery, 2024)
Abstract Background The effects of unilateral submandibular gland excision on the size of the contralateral gland are not well understood, with no human studies reported to date. This study aims to investigate the impact of unilateral submandibular gland excision on the contralateral gland’s size, providing insights into compensatory mechanisms and their clinical implications. Method This retrospective study involved patients with oral cancer who underwent unilateral submandibular gland excision and ipsilateral neck dissection at Gangneung-Wonju National University Dental Hospital between 2008 and 2023. Patients were included if they had preoperative and follow-up 3D radiological images. The contralateral submandibular gland volume was measured using 3D Slicer software on preoperative, post-operative, and follow-up radiographic data. Results The mean volume change of the contralateral submandibular gland was 1.35 ± 2.06 cm3, with a mean change ratio of 1.18 ± 0.24. These changes were statistically significant (p = 0.006). Other factors such as age, gender, and radiotherapy did not significantly affect the volume change ratio (p > 0.05). Conclusion The contralateral submandibular gland exhibits a statistically significant increase in volume following unilateral gland excision, indicating compensatory hypertrophy. This morphological adaptation should be considered in post-operative care and surgical planning for oral cancer patients to optimize outcomes.